Phubbing Behaviour: An Analysis of Triggers and the Impact on Social Interaction in the Digital Age - Hanum Aisya Ranie (IAIN Madura, 2026)
This study examines phubbing as a social phenomenon through the framework of politeness theory, focusing on how it triggers Face Threatening Acts (FTA) and the factors shaping individuals’ responses. Previous research has primarily explored the psychological and relational impacts of phubbing, limited attention has been given at how individuals negotiate face in naturally occurring interactions. To fill this gap, this study uses a qualitative method with semistructured interviews with 25 people aged 15-30 who have been phubbed. The data were analyzed using thematic analysis to identify types of FTA and contributing factors. This study aims to explore the types of face threats caused by phubbing and the factors influencing individuals’ responses to such behavior. The findings show that phubbing can threats positive and negative face. Positive face threats involve feelings of being ignored and unappreciated, leading to indirect responses, while negative face threats involve irritation and disrupted autonomy, prompting more direct reactions. Additionally, the study identifies several key factors influencing responses, including relational closeness, interlocutor personality, prior consent, and conversational context. This study highlights phubbing as a face threat that provokes diverse response patterns influenced by interpersonal and situational variables. These results enhance comprehension of how individuals perceive and react to phubbing in routine communication.